Society's Perceptions toward Zakat Distribution in Micro-Economic Empowerment - Tsalis Syaifuddin (Jurnal Penelitian, 2021)
Recently, there are more and more zakat management institutions offering progressive programs. One of them is micro-economic development that encourages the community's economic sector. However, there are still many Muslims who do not know about that. This study aims to capture the public's perception of the distribution of zakat. It focused on micro-economic empowerment programs. This study uses a descriptive quantitative approach through a survey method with a sample of 1129 respondents. Indonesian people already understand the obligations of Muslims. But, this awareness is still lacking. The openness and transparency of each distribution and management of zakat funds will greatly determine public perceptions and influence the subsequent programs. Zakat institutions must be professional and have a positive impact on mustahiq. They have to give assistance and guidance to them in managing trading businesses as micro-economic empowerment.